2009
DOI: 10.1074/jbc.m109.018028
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Nucleolin as a c-myc G-quadruplex-binding Protein

Abstract: myc is a proto-oncogene that plays an important role in the promotion of cellular growth and proliferation. Understanding the regulation of c-myc is important in cancer biology, as it is overexpressed in a wide variety of human cancers, including most gynecological, breast, and colon cancers. We previously demonstrated that a guanine-rich region upstream of the P1 promoter of c-myc that controls 85-90% of the transcriptional activation of this gene can form an intramolecular G-quadruplex (G4) that functions as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
336
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(352 citation statements)
references
References 95 publications
15
336
1
Order By: Relevance
“…Deficiencies of certain G-quadruplex resolving helicases result in abnormal mRNA deadenylation and decay and in perturbed telomere maintenance and cellular DNA replication, leading to cancer (87). In addition, it was reported recently that nucleolin stabilizes the G-quadruplex within the c-myc promoter and inhibits transcription (88). Interestingly, nucleolin interacts with G-rich sequences in UTRs or the coding region of a lot of mRNAs and was found to enhance their translation (89), suggesting that nucleolin might function as a RNA-G-quadruplex interacting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies of certain G-quadruplex resolving helicases result in abnormal mRNA deadenylation and decay and in perturbed telomere maintenance and cellular DNA replication, leading to cancer (87). In addition, it was reported recently that nucleolin stabilizes the G-quadruplex within the c-myc promoter and inhibits transcription (88). Interestingly, nucleolin interacts with G-rich sequences in UTRs or the coding region of a lot of mRNAs and was found to enhance their translation (89), suggesting that nucleolin might function as a RNA-G-quadruplex interacting factor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work revealed that nucleolin had high affinity to G-quadruplex structure (27), including the sequences in the 5Ј-UTR region of hif-1␣ mRNA. The study reported here provided in vivo evidence for the physical interaction between nucleolin and hif-1␣ mRNA using RNA-IP assay with nucleolin antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleolin has been found to bind to the mRNA of several important genes, including p53 (24), bcl-2 (25), and bcl-xl (26), leading to regulation on mRNA turnover or translation. Moreover, nucleolin has been shown to have binding activity to a number of G-rich oligonucleotides, like the G-quadruplex structure in the promoter region of c-myc gene (27) and vegf gene (28). Gonzalea et al showed, in an in vitro filter binding assay, that nucleolin bound to the G-quadruplex structure in 5Ј-UTR of hif-1␣ mRNA (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For D r a f t 13 example, NCL has been reported to cooperate with hnRNP D to form the heterodimeric LR1 Gquadruplex-binding complex that transcriptionally activates IgH sequences in B-cells (Dempsey et al 1998;Hanakahi et al 1997). In contrast, NCL binding to and stabilization of a defined G-quadruplex structure within the c-MYC gene promoter contributes to transcriptional repression of this locus, possibly by abolishing binding sites for activating TFs or altering the local chromatin (González et al 2009;González and Hurley 2010). Post-transcriptionally, NCL binding to mRNAs may effect expression of particular proteins, with NCL binding to the p53 mRNA 5'UTR resulting in translational activation, while its binding to gadd45α mRNA in response to arsenite treatment and K294-SUMOylation blocks the degradation of this transcript (Takagi et al 2005;Zhang et al 2015).…”
Section: Ncl Throughout the Cell -Nucleolus Nucleoplasm Cytoplasm Amentioning
confidence: 99%